Design for a longer photoinduced charge separation and improved visible-light-driven H2 generation through structure reversal and oxygen vacancies via Ni substitution into ZnFe2O4 spinel. Issue 14 (15th July 2021) - Son, Namgyu; Lee, Junhee; Yoon, Taeho; Kang, Misook
Abstract: The objective of this study was to replace some of the metal ions in the n-type zinc ferrite spinel lattice with Ni 2+ ions to evaluate its catalytic behavior during water splitting. XPS and Raman spectroscopy revealed that the substituted Ni 2+ ions were preferentially located at the octahedral (Oh) sites in the zinc ferrite spinel lattice, rather than the tetrahedral (Td) sites. When the amount of substituted Ni 2+ was >0.6 mol, the crystal structure was converted to an inverse spinel structure. Ni 2+ substitution resulted in the formation of oxygen vacancies in the spinel lattice. With Ni 2+ substitution, the bandgap state changes from direct to indirect. The TRPL, IMVS, and IMPS analyses revealed the carrier diffusion length, e − /h + recombination time, and charge transport rate for the Zn1-x Nix Fe2 O4 inverse spinel. The electrons excited from the valence bands (VBs) to the CBs (O 2p → Fe 3+ 3d) moved to Ni 2+ 3d (Fe 3+ 3d → Ni 2+ 3d) and, subsequently, the longer carrier diffusion length suppressed e − /h + recombination. Eventually, an optimum hydrogen production of 19.2 μmol g −1 was achieved using the Zn0.4 Ni0.6 Fe2.0 O4 catalyst for a 10 h-hydrogen evolution reaction in neutral water splitting, without any sacrificial agent under visible light; Zn0.4 Ni0.6 Fe2.0 O4 exhibited a four-fold improvement compared to ZnFe2 O4 . The material did not significantly deteriorate the catalytic performance, even after six regeneration experiments, and the catalyst material was separated using a magnet after the reaction. Thus, the goal of this study was to develop a simple, eco-friendly, and efficient catalyst via partial cation substitution in the spinel structure. Highlights: Formation of an inverse spinel structure by inserting more than 0.6 mol of Ni. Photoinduced charge separation was maintained in the Ni-inverse spinel catalyst. Water is effectively split, without any sacrificial agent in the Ni-inverse spinel catalyst. The catalyst containing magnetic iron is separated via a magnet after water splitting.